2016
DOI: 10.1136/bcr-2016-216366
|View full text |Cite
|
Sign up to set email alerts
|

Waardenburg-Shah Syndrome: a rare case in an Indian child

Abstract: A 7-year-old male child presented with a history of discolouration of right eye since birth. On examination visual acuity was 6/6 on Snellen's chart in both eyes; anterior segment was within normal limits except for the brilliant blue discolouration of the inferior quadrant and superior quadrant of right iris and left eye iris, respectively. Both eyes had a clear lens and fundus findings were within normal limits. A detailed history from parents revealed that the child had difficulty in hearing and slurring of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(4 reference statements)
1
1
0
1
Order By: Relevance
“…with our study 6. As per study of Sharma et al of a case study of two cases of Waardenburg syndrome showed Type III and Type IV are rare compared to Type I and Type II which had two cases of Type II Waardenburg syndrome which corelates with our study of four cases showing two of each Type I and II cases 7. …”
supporting
confidence: 88%
“…with our study 6. As per study of Sharma et al of a case study of two cases of Waardenburg syndrome showed Type III and Type IV are rare compared to Type I and Type II which had two cases of Type II Waardenburg syndrome which corelates with our study of four cases showing two of each Type I and II cases 7. …”
supporting
confidence: 88%
“…Waardenburg syndrome has been previously reported in the paediatric population. Ng et al and Pattebahadur et al reported an association of Hirschsprung disease with Waardenburg syndrome 4 5. There is a paucity of literature on the association of neurodevelopmental conditions with this genetic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…(32) Além disso, um dos primeiros sintomas que pode aparecer nessa doença é uma descoloração azulada dos olhos. (33) Na SW, podem ser encontradas a heterocromia parcial, total ou segmentar da íris, que pode ser tanto unilateral como bilateral. (1)…”
Section: Síndrome De Waardenburgunclassified